Effect of Corrosion Damage on the Fatigue Behavior of S460NL High-Strength Steel under Cyclic Loading (Fracture and Structural Integrity, 2026)
The present study investigates the influence of corrosion exposure on the fatigue behavior of S460NL high-strength structural steel, a material that is frequently utilized in offshore and civil engineering structures. Accelerated corrosion was simulated under controlled laboratory conditions for exposure periods of 3 days, 6 days, and 6 + 3 days, in addition to specimens subjected to natural atmospheric corrosion. To this end, fatigue tests were performed to obtain S–N curves, and the results were evaluated using Basquin's law and the probabilistic Castillo–Canteli model. The findings indicate that corrosion has a substantial impact on fatigue resistance. The endurance limit exhibited a decline from 214 MPa for the reference specimens to 176 MPa following three days of corrosion, 135 MPa after six days, and approximately 92 MPa after combined corrosion exposure, signifying a reduction of up to 57%. Fractographic observations revealed that corrosion pits act as stress concentrators, thereby promoting early crack initiation. A discernible correlation was identified between corrosion mass loss and normalized endurance limit.These findings highlight the importance of considering corrosion effects in fatigue life assessment and structural design of high-strength steel components.
Keywords: S460 NL; Fatigue; Corrosion; S-N curve; Canteli model; Basquin law